PERFORMA REPRODUKSI SAPI BIBIT BRAHMAN IMPOR PEDIGREE CERTIFICATE DI BALAI PEMBIBITAN TERNAK UNGGUL DAN HIJAUAN PAKAN TERNAK SEMBAWA SUMATERA SELATAN - , HASWITA FITRI AMALIA; , Prof. drh Aris Junaidi, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to determine the reproductive performance of Brahman cattles Pedigree Certificate which were imported from Australia and being kept in Balai Pembibitan Ternak Unggul dan Hijauan Pakan Ternak (BPTU-HPT) Sembawa, South Sumatra. A total of 191 imported Australian Brahman cattles in Balai Pembibitan Ternak Unggul dan Hijauan Pakan Ternak (BPTU-HPT) Sembawa were used for this research. The reproductive performance of beef cattle was measured based on one year data of services per conception (S/C) and postpartus estrous (EPP). Reproductive performance of Brahman cows showed S/C 16,58 Â± 83,5 and EPP 169,51 Â± 0,42 days. Based on the result, reproductive performance of Brahman cows at BPTU-HPT Sembawa is still not optimal.